PENGARUH PROMOSI DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA CAFE FOODHOUSE DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABLE MODERATING - Putri, Dinda Purnama; Karnadi, Karnadi; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2024)
A cafe is a place to relax and chat where visitors can order drinks and food. Cafes have the potential for a solid national economic base and labor absorption that can impact a region's economy. This study aimed to analyze the effect of promotion and brand image on purchasing decisions, with consumer satisfaction as a moderating variable. The population in this study were Foodhouse consumers in Situbondo. The sampling technique was determined by simple random sampling. This study's data analysis and hypothesis testing used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that promotion has a significant positive effect on purchasing decisions, brand image has a positive but insignificant impact on buying decisions, customer satisfaction negatively weakens the relationship between the influence of promotion on buying decisions, customer satisfaction positively weakens the relationship between the influence of brand image on purchasing decisions.